The role of mitochondria in the pathogenesis of the "complex" wound process - A. A. Supilnikov; E. A. Ledovskikh; N. M. Dzhamalova; L. A. Trusova; A. A. Starostina; R. R. Yunusov; B. I. Yaremin (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
Wound healing is a complex biological process involving various cells, mediators, and components of the extracellular matrix involved in the processes of coagulation, inflammation, angiogenesis, epithelialization, and fibroplasia. Wound healing is described by four interrelated phases: hemostasis, inflammation, proliferation and remodeling. Each of the phases has its role at the molecular and tissue levels, and if a defect occurs in the chain of one of the phases of the wound healing process, the healing process is disturbed and a chronic wound condition occurs. Various factors such as infections, arterial and venous circulatory disorders, type 2 diabetes and chronic inflammation contribute to this. Prolonged non-healing wounds represent an urgent problem of modern medicine. Oxidative stress plays a crucial role in the pathogenesis of chronic wounds. In this review the pathogenesis of chronic wounds and its involvement of reactive oxygen species (ROS), oxidative stress, the role of mitochondria in ROS generation as well as the prospects of mitochondrial-directed antioxidants in the treatment of chronic wounds are considered.